2012
DOI: 10.1037/a0028457
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prior knowledge on incidental category learning.

Abstract: This article describes 5 experiments investigating the role of prior knowledge in incidental category learning. Experiments 1 to 3 showed that prior knowledge improved learning only if the categories in a given set were related to contrasting themes; there was no consistent knowledge effect if the categories were related to the same theme. Experiments 4 and 5 showed that diagnostic verbal labels facilitated the learning of non-thematic categories but provided no additional benefit when the categories were alre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This buttressed learning beyond what has been observed for these same stimuli under passive, unsupervised learning conditions (Emberson et al, 2013; Wade & Holt, 2005). Nevertheless, there is evidence that quite complex perceptual categories can be acquired through unsupervised learning (for examples in the visual domain see Clapper, 2012; Love, 2002). It will be important to unravel the relative influence of stimulus input distributions, categorization training task, the influence of an active task, and the presence of different types of feedback in future work.…”
Section: Discussionmentioning
confidence: 99%
“…This buttressed learning beyond what has been observed for these same stimuli under passive, unsupervised learning conditions (Emberson et al, 2013; Wade & Holt, 2005). Nevertheless, there is evidence that quite complex perceptual categories can be acquired through unsupervised learning (for examples in the visual domain see Clapper, 2012; Love, 2002). It will be important to unravel the relative influence of stimulus input distributions, categorization training task, the influence of an active task, and the presence of different types of feedback in future work.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of the category invention framework, the main difference between supervised and unsupervised learning is that providing people with the category membership of each instance, as in supervised learning, eliminates the discovery/aggregation problem that is so central to unsupervised learning. Consistent with this, Clapper and Bower (2002) and Clapper (2012) showed that providing diagnostic category labels with each instance in the exemplar-memory task substantially improved learning in interleaved conditions-that is, much or all of the interleaving effect was eliminated by providing diagnostic labels.…”
Section: Relation To Supervised Learningmentioning
confidence: 53%
“…Means and standard deviations for consistent and variable features are shown in Table 1, while consistent feature recalls are shown plotted over trials in Figure 2. Following procedures reported in Clapper (2007Clapper ( , 2012, the bottom 25% of participants from each condition (a total of six participants, three per condition) were excluded from Figure 2 and all subsequent data analyses. This procedure is intended to correct for inattentive responding (Meade & Craig, 2012), which can add random noise to the data and substantially decrease the power of an experiment (e.g., Osborne & Blanchard, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…In these studies, researchers have taken the approach of examining learning in contexts in which participants interact actively with the category-relevant information in the context of an engaging primary task (Clapper, 2012;Gabay et al, 2015;Lim et al, 2019;Lim & Holt, 2011;Protopapas et al, 2017;Seitz et al, 2010;Vlahou et al, 2012;Wade & Holt, 2005). Notably, this primary task does not require overt category decisions, instruction about the existence of categories, or explicit feedback about categorization.…”
Section: Incidental Category Learningmentioning
confidence: 99%